Development of an information system for processing astronomical images using cloud technologies - Hadzhyiev, E. R. (ХНУРЕ, 2024)
In this study we overview an information system designed to process astronomical images using cloud technologies, emphasizing the system's architecture and its deployment using these technologies. The system, leveraging cloud infrastructure, offers a scalable and efficient solution for handling large volumes of astronomical data, including blurred images captured by CCD cameras. The core of our system's innovation lies in its cloud-based deployment, which facilitates scalability, accessibility, and the efficient processing of data. This approach not only improves the quality of astronomical images but also accelerates the analysis and interpretation of celestial phenomena. Flexible solution architecture allows for the potential incorporation of other algorithms tailored to specific astronomical image processing needs.
Keywords: information system; cloud technologies